Interpretable Bangla fake news classification using BERT and traditional machine learning approaches - Anan, Ramisa; Modhu, Elizabeth Antora; Suter, Arjun; Sneha, Ifrit Jamal (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.